Development of an Acid Base E-Module based on Flip Book Vocational School Industrial Pharmacy Skills Program - A. Afrinaramadhani Hatta; Nur Indah Sari; Fandi Ahmad; Zulqifli Alqadri (Edumaspul: Jurnal Pendidikan, 2024)
The development of e-modules aims to become an effective learning resource for students, especially in studying acid-base material at the vocational school level. This research aims to evaluate the validity and responses of students to e-modules on acid-base material created using the Flip Book application. The research method used is development research with the ADDIE model. Data was analyzed quantitatively descriptively. The object of the trial is limited to practical aspects, namely class XI students in the Industrial Pharmacy skills program. The research results show that the e-module developed using Flip Book has been validated by material experts, media experts, chemistry subject teachers and pharmaceutical expertise programs, and laboratory assistants, with a score of 95.17%, indicating a very good category and suitable for use in learning . The results of the e-module practicality test of 3.58 are included in the very good category.